Uniform Requirements for Manuscripts Submitted to Biomedical Journals: Writing and Editing for Biomedical Publication Updated April 2010 (Bangladesh Journal of Child Health, 2013)
DOI: http://dx.doi.org/10.3329/bjch.v37i1.15353 BANGLADESH J CHILD HEALTH 2013; VOL 37 (1) : 52-73